Pengembangan Produk UMKM Tahu Melalui Pemanfaatan Platform Facebook - Ngafifudin Asrofi; Muhamad Rifqi Firdaus; Bobby Ahmad Fahrezy; Bintis Tianatud Diniati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In this era, many people in Plosokandang Village have not utilized digital technology, even though small businesses play an important role in economic development. One example is Mr. Imin's tofu business. Through a community empowerment program for MSME owners in Plosokandang Village, Tulungagung Regency, entrepreneurs now have more insight into marketing, both offline and through social media such as Facebook. Social media helps them reach a wider range of consumers and meet market demand. The utilization of digital technology allows direct interaction with consumers, obtaining feedback, and adjusting products and marketing strategies. This program is expected to increase the competitiveness of MSMEs in the domestic market while supporting the sustainable strengthening of the community economy. With new skills, MSME owners are expected to be more proactive in facing the challenges of the digital era and support regional economic growth.s